2009
DOI: 10.1073/pnas.0812242106
|View full text |Cite
|
Sign up to set email alerts
|

Prevascularization of cardiac patch on the omentum improves its therapeutic outcome

Abstract: The recent progress made in the bioengineering of cardiac patches offers a new therapeutic modality for regenerating the myocardium after myocardial infarction (MI). We present here a strategy for the engineering of a cardiac patch with mature vasculature by heterotopic transplantation onto the omentum. The patch was constructed by seeding neonatal cardiac cells with a mixture of prosurvival and angiogenic factors into an alginate scaffold capable of factor binding and sustained release. After 48 h in culture,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
256
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 321 publications
(261 citation statements)
references
References 37 publications
5
256
0
Order By: Relevance
“…Many of the proposed applications for hPSC-derived cardiomyocytes may require three-dimensional engineered tissue to more accurately reflect drug responses and function in the adult heart. Recent studies suggest that appropriate combinations of cardiac cells, endothelial cells and fibroblasts must be incorporated into such tissue constructs for them to function best in vitro or in vivo [23][24][25] . Our ability to generate pure myocyte and nonmyocyte populations will allow for the generation of engineered constructs consisting of varying proportions of different cell types, enabling us to determine the optimal combination of each required to form heart tissue with structural and functional properties most similar to that of the human heart.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the proposed applications for hPSC-derived cardiomyocytes may require three-dimensional engineered tissue to more accurately reflect drug responses and function in the adult heart. Recent studies suggest that appropriate combinations of cardiac cells, endothelial cells and fibroblasts must be incorporated into such tissue constructs for them to function best in vitro or in vivo [23][24][25] . Our ability to generate pure myocyte and nonmyocyte populations will allow for the generation of engineered constructs consisting of varying proportions of different cell types, enabling us to determine the optimal combination of each required to form heart tissue with structural and functional properties most similar to that of the human heart.…”
Section: Discussionmentioning
confidence: 99%
“…Sekine et al (28) proposed in vitro fabrication of cardiac tissue with perusable blood vessels using a muscle tissue with a connectable artery and vein as a bed perfused in a bioreactor. Dvir et al (29) constructed a vascularized cardiac patch using both survival and angiogenic factors by first implanting the patch on the omentum. Controlled delivery of proangiogenic factors from growth factoreluting scaffolds has been shown to induce host vessel ingrowth into the implant (30), whereas EC seeding has been attempted to promote additional vascularization on implantation (31).…”
Section: Discussionmentioning
confidence: 99%
“…Lesman et al (28) transplanted prevascularized constructs containing hESC-derived cardiomyocytes, HUVECs, and MEFs and showed that they formed viable, perfused grafts in hearts of immunosuppressed rats. Dvir et al (29) created a neonatal rat cardiomyocyte patch and prevascularized it on the omentum, prior to transplanting it onto the heart. They report these patches integrated structurally and electrically with the host heart.…”
Section: Shortening Contractions Stimulated By Electrical Pacing In Wmentioning
confidence: 99%